A Glutamine Transport Gene, glnQ, Is Required for Fibronectin Adherence and Virulence of Group B Streptococci - Tamura, Glen S. (American Society for Microbiology, 2002)
Group B streptococci (GBS) are a leading cause of neonatal sepsis and meningitis. GBS adhere to fibronectin when it is attached to a solid phase. We isolated a Tn917 transposon mutant, COH1-GT1, which shows decreased adherence to fibronectin. COH1-GT1 also shows decreased adherence to and invasion of respiratory epithelial cells in vitro and decreased virulence in vivo. COH1-GT1 contains a Tn917 insertion in a homolog of glnQ, a gene from Escherichia coli which is required for glutamine transport and codes for a cytoplasmic ATP-binding cassette protein. To confirm that the decreased fibronectin adherence of COH1-GT1 was due to the mutation in glnQ, we constructed COH1-GT2, a strain with a nonpolar site-directed mutation in glnQ. COH1-GT2 showed decreased binding to fibronectin. We also demonstrated that complementation of glnQ in trans restored fibronectin adherence to COH1-GT1. COH1-GT1 shows decreased uptake of radiolabeled glutamine and is resistant to the toxic glutamine analog γ-l-glutamylhydrazide, demonstrating that the glnQ gene is required for glutamine transport in GBS. glnQ lacks a signal sequence and is a cytoplasmic protein in E. coli and thus is unlikely to act as a fibronectin adhesin. glnQ is transcribed in an operon with a putative glutamine permease gene, glnP, which has a novel predicted structure containing three distinct domains linked in a single gene. The first two domains are putative glutamine binding domains with homology to the E. coli periplasmic glutamine binding gene glnH. The third is a putative permease domain with homology to the E. coli glutamine permease gene glnP. RT-PCR analysis demonstrated that glnP and glnQ are contained within a single transcript. Transcription of scpB, encoding the only known fibronectin-binding adhesin of GBS, is unaffected. We speculate that glnQ may regulate expression of fibronectin adhesins by affecting cytoplasmic glutamine levels and that regulation may be posttranscriptional.